PEMANFAATAN QUIZIZZ DALAM DIGITAL GAME BASED LEARNING PADA MATA PELAJARAN BAHASA INGGRIS KELAS 5 SD NEGERI CIPONDOH 2 KOTA TANGERANG - Nanda Citra Kumarani; Dayu Retno Puspita; Asih Rosnaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Use of Quizizz in Digital Game-Based Learning in English Lessons for Grade 5 Students at SDN Cipondoh 2 in Tangerang City. This study describes the use of the Quizizz application for Digital Game-Based Learning in fifth-grade English classes at SDN Cipondoh 2, Tangerang City. The research background highlights a problem of low student interest and enthusiasm in learning English due to the use of conventional teaching methods. This study uses a descriptive qualitative approach with the researcher as the key instrument and was conducted at SDN Cipondoh 2, Tangerang City. Data was collected through triangulation techniques, including interviews, observations, and documentation, focusing on extracting meaning from objective conditions in the field. The subject of this study was the fifth-grade English teacher.The results show that using Quizizz as a Digital Game-Based Learning tool successfully created a more interactive, engaging, and enjoyable learning atmosphere. The advantage of Quizizz is that it functions not only as an evaluation tool but also as an interactive learning medium. Its ease of access and features allow students to focus on the material. The study also identified a weakness: for students who were slow to understand or master the educational game, the teacher adjusted the method by presenting simplified, easy-to-understand material relevant to daily life and using concrete examples.